A phase III randomized controlled trial comparing surgery plus adjuvant chemotherapy with preoperative chemoradiotherapy followed by surgery plus adjuvant chemotherapy for locally recurrent rectal cancer: Japan Clinical Oncology Group study JCOG1801 (RC-SURVIVE study). (15th May 2020) - Kadota, Tomohiro; Tsukada, Yuichiro; Ito, Masaaki; Katayama, Hiroshi; Mizusawa, Junki; Nakamura, Naoki; Ito, Yoshinori; Bando, Hideaki; Ando, Masahiko; Onaya, Hiroaki; Fukuda, Haruhiko; Kanemitsu, Yukihide
Abstract: A randomized phase III trial was initiated in Japan in August 2019 to confirm the superiority of preoperative chemoradiotherapy followed by surgery plus adjuvant chemotherapy compared to the standard treatment, i.e. surgery plus adjuvant chemotherapy, for locally recurrent rectal cancer in local relapse-free survival. In all, 110 patients from 43 Japanese institutions will be recruited over a period of 6 years. Eligible patients would be registered and randomly assigned to each group with an allocation ratio of 1:1. The primary endpoint is local relapse-free survival. The secondary endpoints are overall survival, relapse-free survival, proportion of local relapse, proportion of distant relapse, proportion of patients with pathological R0 resection, response rate of preoperative chemoradiotherapy (preoperative chemoradiotherapy arm), pathological complete response rate (preoperative chemoradiotherapy arm), proportion of patients who completed the protocol treatment, incidence of adverse events (adverse reactions) and quality of life after surgery. This trial has been registered at the Japan Registry of Clinical Trial: jRCTs031190076 [https://jrct.niph.go.jp/latest-detail/jRCTs031190076 ] and ClinicalTrials.gov : NCT04288999 [https://clinicaltrials.gov/ct2/show/NCT04288999 ]. Abstract : A multicenter randomized phase III trial was initiated to confirm the superiority of preoperative chemoradiotherapy followed by surgery plus adjuvant chemotherapy over the standard treatment for locally recurrent rectal cancer.